2018
DOI: 10.3390/ijms19040983
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Blueberry miRNAs and Their Targets Based on High-Throughput Sequencing and Degradome Analyses

Abstract: miRNAs are important regulators of plant gene expression. To better characterize their functions, we applied high-throughput sequencing and degradome analyses to investigate three blueberry (Vaccinium ashei) tissues. A total of 127 known and 101 novel miRNAs were identified. Moreover, 141 targets for 42 known and 19 novel miRNAs were experimentally validated by degradome sequencing. A functional analysis of these miRNA targets revealed they were associated with diverse biological activities and several pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The complement of miRNAs has been identified in blueberries using high-throughput sequencing. For example, 412 conserved miRNAs belonging to 29 families were identified in fruits from rabbiteye blueberry ( Yue et al, 2017 ); similarly, 127 known and 101 novel miRNAs were identified from flowers, young fruits, and ripe fruits of rabbiteye blueberry ( Li G. et al, 2018 ). In highbush blueberry, 84 known miRNAs and 16 novel miRNAs were identified from fruits, with 10 miRNAs from miR166 family ( Hou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complement of miRNAs has been identified in blueberries using high-throughput sequencing. For example, 412 conserved miRNAs belonging to 29 families were identified in fruits from rabbiteye blueberry ( Yue et al, 2017 ); similarly, 127 known and 101 novel miRNAs were identified from flowers, young fruits, and ripe fruits of rabbiteye blueberry ( Li G. et al, 2018 ). In highbush blueberry, 84 known miRNAs and 16 novel miRNAs were identified from fruits, with 10 miRNAs from miR166 family ( Hou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the length of sRNA varies among different species. The sRNA length of blueberry [ 37 ], sweet potato [ 38 ], and tea tree [ 39 ] is at most 24 nt, whereas that of poplar [ 40 ], soybeans [ 41 ], and tomato [ 42 ] is at most 21 nt, and high-throughput sequencing data showed that the sRNA length in 12 databases is at most 24 nt, followed by 21 nt ( Figure 1 ), which is similar to that of Ramat Ju [ 43 ]. The reported typical sRNA distribution patterns are extremely similar.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them are widely involved in the plant growth and development, metabolism, hormone regulation, and various biological and abiotic stresses (Li et al, 2020 ). Presently, miR828, miR858, miR156, miR159, miR157, miR160, miR172, miR393, miR396, miR824, and miR870 in Litchi chinensis (Liu et al, 2017 ), Punica granatum (Saminathan et al, 2016 ), Hylocereus monacanthus (Chen et al, 2020 ), Raphanus sativus (Gao et al, 2019 ), Lycium ruthenicum (Qi et al, 2020 ), Diospyros kaki (Luo et al, 2015 ), Vaccinium ashei (Li et al, 2018 ), Actinidia arguta (Li et al, 2019 ), and Lonicera edulis (Li et al, 2018 ), respectively, have been found to be involved in the regulation of anthocyanin metabolism. Both miR156h‐3p and miR396a‐3p can target UFGT in L. edulis and significantly negatively correlate with anthocyanin biosynthesis (Cui et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lonicera edulis (Li et al, 2018), respectively, have been found to be involved in the regulation of anthocyanin metabolism. Both miR156h-3p and miR396a-3p can target UFGT in L. edulis and significantly negatively correlate with anthocyanin biosynthesis (Cui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%